2021
DOI: 10.1099/mgen.0.000543
|View full text |Cite
|
Sign up to set email alerts
|

The structure and diversity of strain-level variation in vaginal bacteria

Abstract: The vaginal microbiome plays an important role in human health and species of vaginal bacteria have been associated with reproductive disease. Strain-level variation is also thought to be important, but the diversity, structure and evolutionary history of vaginal strains is not as well characterized. We developed and validated an approach to measure strain variation from metagenomic data based on SNPs within the core genomes for six species of vaginal bacteria: Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Lactobacillus species including L. crispatus, L. gasseri, L. jensenii , and L. iners , dominated the primary vaginal microbiota have been associated with reproductive disease ( 15 ). 16S rRNA sequencing is a method widely applied for microbiology detection in the laboratory, while general bacterial culture is commonly implemented in clinical use ( 31 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus species including L. crispatus, L. gasseri, L. jensenii , and L. iners , dominated the primary vaginal microbiota have been associated with reproductive disease ( 15 ). 16S rRNA sequencing is a method widely applied for microbiology detection in the laboratory, while general bacterial culture is commonly implemented in clinical use ( 31 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus was the primary flora before menopause. Loss of Lactobacillus dominance promotes the colonization by anaerobic bacterial species with an increase in microbial diversity ( 15 ). The decrease in lactobacilli postmenopause leads to opportunistic pathogens, such as Gardnerella, Prevotella, Streptococcus, Escherichia/Shigella becoming the dominant bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ), indicating that the L. crispatus at the initial time point was supplanted by another at the second sampling. It could be that these L. crispatus populations went extinct and were subsequently reestablished or that the population experienced a shift in the dominant strain, as prior studies have indicated these populations are often comprised of multiple strains ( 14 , 19 ). Participant 4 had a L. iners - dominated VMB at the initial time point, which shifted to a community that contained a majority of L. crispatus and a minority of L. iners at the second time point.…”
Section: Observationmentioning
confidence: 99%
“…Interestingly, based on studies of non-human primates (Yildirim et al 2014) and other empirical arguments, Lewis postulates that the "Gardnerella" microbiome type might be the "ancestral state" (cf. Gilbert et al 2021;Tortelli et al 2021). E.g., the lactobacilli dominance is not found in other primates, while women with bacterial vaginosis show similar microbiome compositions to healthy baboons and macaques, but the pH-values still tend to be lower in women with bacterial vaginosis compared to non-human primates (Miller et al 2016).…”
mentioning
confidence: 99%